Gender inequality and development in Nigeria (2007)
This study examines the factors that hinder meaningful development in Nigeria in the midst of abundant human and material resources. Data were obtained from Ibadan, south western, Nigeria through a triangulation of Focus Group Discussion, In-depth Interview and Unobtrusive Observation. The study shows clearly that: (1) a very large majority of Nigerian women are poor and that this explains their ignoble involvement in development; (2) most women are, unwittingly predisposed to the perception and attitude that suggest that their situation in the social system is normal; and (3) the patriarchal ethos of the Nigerian society impinges forcefully on the extent that developmental processes are democratic and socially inclusive. The implication of these findings is that attempts at achieving multidimensional development in Nigeria have been distorted by long years of gender propelled inequality, skepticism and contradictions within the social system. The study has some policy implications. First, there is need to re-orientate Nigerians, especially males, on the need to involve women fully in development. Second, following from the former, is the necessity of dislocating those factors that sustain women exclusion from socio-economic and cultural activities and, ultimately, the development of underdevelopment